Seven habits of highly effective doctors. Issue 3 (May 2016) - Kirby, Roger
Abstract : Recently, I was fortunate enough to be awarded the Sir Clement Price Thomas medal from the Royal College of Surgeons. At the presentation ceremony, I was asked to say a few encouraging words to the many young doctors who were receiving the diplomas that mark the beginning of their careers in surgery. This in brief is what I told them.